Strength and muscle mass in the elderly people from Northeast Brazil (Research, Society and Development, 2021)
This study aimed to measure the strength and muscle mass of elderly people from a small town in northeastern Brazil; investigate differences between sexes and age groups; and correlate strength and muscle mass in the study population. This is an epidemiological, cross-sectional study carried out with 211 elderly people from Aiquara-BA. Handgrip strength (HGS) was measured by a hydraulic dynamometer. Total muscle mass and muscle mass index were estimated by anthropometric equations. The cutoff points for the diagnosis of dynapenia and low muscle mass (MM) were identified by sex (25th percentile of HGS; 20th percentile of muscle mass index). The results show that, in both sexes, the younger elderly had higher HGS and MM. It was also observed that men had higher HGS, total muscle mass and muscle mass index. In that gender, there was also a moderate positive correlation between HGS with total muscle mass and weak with muscle mass index. In women, there was a weak positive correlation between HGS and total muscle mass. Furthermore, it was found that dynapenia and low MM were more prevalent in the elderly aged ≥80 years. The evidence investigated showed that women and the oldest old had lower HGS and MM. In both sexes there was a positive correlation between HGS and MM. Furthermore, dynapenia and MM deficit were more frequent in the oldest old.